Small Molecules Targeting Human N‐Acetylmannosamine Kinase. (27th April 2017) - Hinderlich, Stephan; Neuenschwander, Martin; Wratil, Paul R.; Oder, Andreas; Lisurek, Michael; Nguyen, Long D.; von Kries, Jens P.; Hackenberger, Christian P. R.
Abstract: N ‐Acetylmannosamine kinase (MNK) plays a key role in the biosynthesis of sialic acids and glycosylation of proteins. Sialylated glycoconjugates affect a large number of biological processes, including immune modulation and cancer transformation. In search of effective inhibitors of MNK we applied high‐throughput screening of drug‐like small molecules. By applying different orthogonal assays for their validation we identified four potential MNK‐specific inhibitors with IC50 values in the low‐micromolar range. Molecular modelling of the inhibitors into the active site of MNK supports their binding to the sugar or the ATP‐binding pocket of the enzyme or both. These compounds are promising for downregulation of the sialic acid content of glycoconjugates and for studying the functional contribution of sialic acids to disease development. Abstract : Modulation of sialic acid biosynthesis : Several drug‐like small molecules have been identified as inhibitors of N ‐acetylmannosamine kinase by high‐throughput screening. Validation and molecular modelling show high affinity in the low micromolar range for this important enzyme involved in the biosynthesis of sialic acids.